2015
DOI: 10.1136/bmj.h1225
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of paracetamol for spinal pain and osteoarthritis: systematic review and meta-analysis of randomised placebo controlled trials

Abstract: Objective To investigate the efficacy and safety of paracetamol (acetaminophen) in the management of spinal pain and osteoarthritis of the hip or knee. Design Systematic review and meta-analysis. Data sources Medline, Embase, AMED, CINAHL, Web of Science, LILACS, International Pharmaceutical Abstracts, and Cochrane Central Register of Controlled Trials from inception to December 2014. Eligibility criteria for selecting studies R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
295
0
23

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(323 citation statements)
references
References 56 publications
5
295
0
23
Order By: Relevance
“…[2] There are little side effects for healthy adults taking regular doses of up to 4000 mg (e.g., gastrointestinal upset) but there is some administration cautions especially in cases of liver diseases, hypersensitivity to acetaminophen, severe renal impairment, I.V administration, chronic high dose and risk of hepatotoxicity is higher in alcoholism. [5,6] Due to paracetamol present in many OTC drugs and checking of drugs labels is significant necessity to ensure that total daily dose of paracetamol from different products does not encroach maximum daily dose. [6] NSAID is used to treat pain and reduce inflammation.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 99%
“…[2] There are little side effects for healthy adults taking regular doses of up to 4000 mg (e.g., gastrointestinal upset) but there is some administration cautions especially in cases of liver diseases, hypersensitivity to acetaminophen, severe renal impairment, I.V administration, chronic high dose and risk of hepatotoxicity is higher in alcoholism. [5,6] Due to paracetamol present in many OTC drugs and checking of drugs labels is significant necessity to ensure that total daily dose of paracetamol from different products does not encroach maximum daily dose. [6] NSAID is used to treat pain and reduce inflammation.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 99%
“…Other studies indicate that acetaminophen has a general blunting effect on individuals' emotional processing 51) and that acetaminophen is not effective in the treatment of low back pain and provides minimal short-term benefit for people with osteoarthritis 52) . There are some studies opposing the above opinions.…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…Acetaminophen may be prescribed as a therapeutic trial, although recent evidence from randomized trials has shown that it is not effective for reducing pain, disability or recovery time in people with acute low-back pain. 9 Nonsteroidal anti-inflammatory drugs (NSAIDs) may be prescribed as a therapeutic trial, given that the evidence has shown small improvement in pain intensity. 10 However, Choosing Wisely Canada recommends against prescribing NSAIDs (including cyclo-oxygenase type 2 inhibitors) for patients with hypertension because of potential cardiovascular and renal complications (Box 1).…”
Section: What Nonpharmacologic Therapy Should Be Prescribed For Thismentioning
confidence: 99%